A doxology to Christ (Rev. 1:5e-6) - J. C. de Smidt (In die Skriflig, 2006)
Revelation 1:5e-6 is a doxology, an eulogy on the characteristics (attributes) of Christ. Christ’s churches celebrate the enduring love of Christ, who by a once-and-for-all historical act redeemed them from enslavement to sin. Through this redemptive achievement Christ obtained royal and priestly prerogatives for believers in the present. The meaning of this doxology is investigated from a “heilgeschichtlich” and covenantal context. The acts of Christ are framed by the acts of God; God thus is the “Principium Essendi”. The point of departure in this article is that an ontological relationship exists between the theologia naturalis and the theologia supra- naturalis in the final phase of God’s kingdom.